Gastroschisis and late-onset neonatal sepsis in a tertiary referral center in Southeastern Brazil - Juliana Zoboli Del Bigio; Ana Cristina Aoun Tannuri; Mário Cícero Falcão; Werther Brunow de Carvalho; Felipe Yu Matsushita (Elsevier, 2022)
Objectives: To analyze late-onset sepsis and to describe the etiological agents in newborns with gastroschisis. Methods: A retrospective cohort, including newborns with gastroschisis whose admissions occurred in the period between January 2012 to December 2018 in a tertiary referral center. Maternal and newborn characteristics, surgical procedures and evolution in hospitalization were verified. A bivariate analysis was performed with patients with proven late-onset neonatal sepsis and according to the simple or complex gastroschisis category, the prevalent microorganisms in positive cultures were identified, statistical tests were carried out and the significance level adopted was p < 0,05. Results are presented in proportions, averages and standard deviation or medians. The level of significance adopted was p < 0.05. Results: 101 newborns were analyzed, 45 (44.5%) were confirmed late-onset sepsis. The median birth weight was 2285+498 grams, and the gestational age was 35.9 +1.74weeks. The incidence of complex gastroschisis was 17.8%, the hospitalization time was 48.2+29.67 days and mortality was 9.9%. The newborns were divided into 2 groups: Group 1: late-onset sepsis (44.6%), and Group 2: no late-onset sepsis. The presence of complex gastroschisis was a factor associated with infection (p < 0.009). Fasting time (p < 0.001), parenteral nutrition time (p < 0.001), time to achieve full diet (p < 0.001), and hospitalization stay (p < 0.001) were higher in group 2. Gram-positive were the most frequent (51.1%), followed by Gram-negative (20%), and fungi (4.4%). Conclusions: Newborns with gastroschisis have a higher risk of evolving with late-onset sepsis, despite this study did not calculate the risk of sepsis statistically, and the main germs detected by cultures were gram-positive bacteria, specifically Staphylococcus epidermidis.